Alternative polyadenylation events in epithelial cells sense endometritis progression in dairy cows - Meagan J. STOTTS; Yangzi ZHANG; Shuwen ZHANG; Jennifer J. MICHAL; Juan VELEZ; Bothe HANS; Martin MAQUIVAR; Zhihua JIANG (Journal of Integrative Agriculture, 2023)
Endometritis (inflammation of the endometrial lining) is one of the most devastating reproductive diseases in dairy cattle, resulting in substantial production loss and causing more than $650 million in lost revenue annually in the USA. We hypothesize that alternative polyadenylation (APA) sites serve as decisive sensors for endometrium health and disease in dairy cows. Endometrial cells collected from 18 cows with purulent vaginal discharge scored 0 to 2 were used for APA profiling with our whole transcriptome termini site sequencing (WTTS-seq) method. Overall, pathogens trigger hosts to use more differentially expressed APA (DE-APA), more intronic DE-APA, more DE-APA sites per gene and more DE-genes associated with inflammation. Host CD59 molecule (CD59), Fc fragment of IgG receptor IIa (FCGR2A), lymphocyte antigen 75 (LY75) and plasminogen (PLG) may serve as initial contacts or combats with pathogens on cell surface, followed by activation of nuclear receptor subfamily 1 group H member 4 (NR1H4) to regulate AXL receptor tyrosine kinase (AXL), FGR proto-oncogene, Src family tyrosine kinase (FGR), HCK proto-oncogene, Src family tyrosine kinase (HCK) and integrin subunit beta 2 (ITGB2) for anti-inflammation. This study is the first to show significance of cilium pathways in endometrium health and animal reproduction. MIR21 and MIR30A would be perfect antagonistic biomarkers for diagnosis of either inflammation or anti-inflammation. These novel findings will set precedent for future genomic studies to aid the dairy industry develop new strategies to reduce endometritis incidence and improve fertility.